Impact Of Social Interaction Constructs on User Engagement On Linkedin As A Social Media Platform For Undergraduate Students In Indonesia (Journal of Business and Management, 2022)
In recent years, social media has shifted from exclusively personal use to platforms that recruiters and companies alike frequent in order to establish work connections and find potential hires. As such, LinkedIn, a professional social media platform, holds promise as a tool to actively improve the opportunity for younger users (i.e.: undergraduate/undergraduate-adjacent individuals) in Indonesia to obtain jobs and build professional connections. However, as of current the appeal of LinkedIn for this target demographic is limited. This research aims to determine what factors impact user engagement on LinkedIn, the factors being adapted from Di Ganggi & Wasko (2016)’s social media engagement theory. The factors tested include personalization, social accessibility, perceived risk, and transparency. The dataset for the research was obtained via online questionnaire, distributed via convenience sampling to the target demographic of undergraduate/undergraduate-adjacent LinkedIn users. A total of 126 respondents filled out the questionnaire, with 124 entries having been deemed valid. The resulting entries were then processed through PLS-SEM for data analysis via SMART PLS. The results indicate that while personalization and social accessibility have a positive correlation with the level of user engagement on LinkedIn, no significant correlation exists between perceived risk, transparency, and the level of user engagement.